Uncovering the Complexities of Coping: A Qualitative Study on the Challenges Faced by Special Education Teachers in the Sandwich Generation - Cuadra, Jefferson M. (Philippine Social Science Journal, 2023)
This article explored the challenges encountered by Special Education (SPED) teachers who belong to the "sandwich generation," a group of middle-aged adults responsible for caring for their elderly parents and children while maintaining professional obligations. The study employed the Interpretative Phenomenological Analysis (IPA) research method to gather and analyze participant data. The study results reveal that SPED teachers experience physical and mental demands, excessive responsibilities, and obstacles that hinder their self-fulfillment, leading to harsh and challenging circumstances. Nevertheless, these individuals demonstrate spiritual and social resilience through adaptive coping mechanisms, including effective time management, prioritizing quality time with loved ones, and engaging in religious practices. This research provides valuable insights into the unique challenges that SPED teachers in the sandwich generation encounter and suggest strategies for supporting them in their personal and professional lives. These findings are significant for policymakers, educators, and practitioners in special education, as they shed light on the need for targeted support systems that address the complex demands of this population.